2020
DOI: 10.1111/jcmm.15221
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates renal fibroblast‐myofibroblast transdifferentiation and renal fibrosis through miR‐21‐5p regulation

Abstract: Fibroblast‐myofibroblast transdifferentiation (FMT) is widely recognized as the major pathological feature of renal fibrosis. Although melatonin has exerted antifibrogenic activity in many diseases, its role in renal FMT remains unclear. In the present study, the aim was to explore the effect of melatonin on renal FMT and the underlying mechanisms. We established the transforming growth factor (TGF)‐β1 stimulated rat renal fibroblast cells (NRK‐49F) model in vitro and unilateral ureteral obstruction (UUO) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 44 publications
1
21
0
3
Order By: Relevance
“…In addition, we previously demonstrated that a melatonin treatment can suppress renal fibrosis by upregulating miR-4516 in kidney tissues [139], and this is consistent with the widely reported antifibrotic effects of melatonin [140,141,201,202]. More recently, we showed that the melatonin-mediated upregulation of miR-4516 promotes PrP C expression [68].…”
Section: Prp C and Renal Fibrosissupporting
confidence: 86%
“…In addition, we previously demonstrated that a melatonin treatment can suppress renal fibrosis by upregulating miR-4516 in kidney tissues [139], and this is consistent with the widely reported antifibrotic effects of melatonin [140,141,201,202]. More recently, we showed that the melatonin-mediated upregulation of miR-4516 promotes PrP C expression [68].…”
Section: Prp C and Renal Fibrosissupporting
confidence: 86%
“…Renal fibroblasts quiescently reside in renal interstitium and play an essential role in ECM homeostasis for maintaining the kidney ultrastructure and function 61 , 62 . During fibrogenesis, the quiescent fibroblasts are activated and display a spindle-shaped, mesenchymal phenotype, known as myofibroblasts 63 , 64 . In the present study, we found that BHK-21 cells treated with COM-MP secretome were more spindle-shaped and had greater spindle index, indicating that they underwent activation into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…A major marker of PSC activation is the expression of α-sma [ 63 ]. Interestingly, melatonin decreases the expression of this protein in myofibroblasts [ 64 ], endothelial cells [ 65 ], liver [ 66 ] or lung [ 67 ]. These observations support an antifibrogenic action of melatonin in these tissues.…”
Section: Discussionmentioning
confidence: 99%